Temperature Dependency of Nucleation Efficiency of Carbon Nanotubes in PET and PBT. Issue 6 (19th February 2015) - Wurm, Andreas; Herrmann, Anja; Cornelius, Maria; Zhuravlev, Evgeny; Pospiech, Doris; Nicula, Radu; Schick, Christoph
<x xml:space="preserve">Abstract</x> The crystallization behavior of polyethylene terephthalate (PET) and polybutylene terephthalate (PBT) filled with different amount of multi‐walled carbon nanotubes (MWCNT) has been experimentally determined in the entire temperature range between glass transition and melting temperature. Differential fast scanning chip calorimetry, realizing cooling and heating rates of several 1 000 K · s−1, have been applied under isothermal and non‐isothermal conditions. The MWCNTs act as heterogeneous nuclei for both polymers. Increasing filler content speeds up crystallization at low supercooling, where heterogeneous nucleation dominates, for more than one order of magnitude. At high supercooling (crystallization temperature below 120 °C for PET and 70 °C for PBT) crystallization kinetics is independent on MWCNT concentration. Here crystallization via homogeneous nucleation is always determining the overall crystallization kinetics and addition of nucleating agents is not effective anymore. Depending on the processing conditions these observations may be important for structure formation in PET and PBT composites.<inline-graphic xlink:href="ark:/27927/pgjr0sjb2r" content-type="mame201400405-gra-0001" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />